Evaluation of performance of the Omni mode for detecting video capsule endoscopy images: A multicenter randomized controlled trial - Hosoe, Naoki; Watanabe, Kenji; Miyazaki, Takako; Shimatani, Masaaki; Wakamatsu, Takahiro; Okazaki, Kazuichi; Esaki, Motohiro; Matsumoto, Takayuki; Abe, Takayuki; Kanai, Takanori; Ohtsuka, Kazuo; Watanabe, Mamoru; Ikeda, Keiichi; Tajiri, Hisao; Ohmiya, Naoki; Nakamura, Masanao; Goto, Hidemi; Tsujikawa, Tomoyuki; Ogata, Haruhiko (Endoscopy International Open, 2016)
Background and study aims: Olympus recently developed a new algorithm called Omni mode that discards redundant video capsule endoscopy (VCE) images. The current study aimed to demonstrate the non-inferiority of the Omni mode in terms of true positives (TPs) and the superiority of the Omni mode with regard to reading time against a control (ordinary ES-10 system).Patients and methods: This multicenter prospective study included 40 patients with various small bowel diseases. VCE images were evaluated by 7 readers and 3 judging committee members. Two randomly allocated readers assessed the VCE images obtained using the 2 modalities for each patient. The order of the modalities was switched between the 2 readers and the interval between readings by the same reader was 2 weeks. The judging committee predefined clinically relevant lesions as major lesions and irrelevant lesions as minor lesions. The number of TPs for major and minor lesions and the reading times were compared between the modalities. The predefined non-inferiority margin for the TP ratio of the Omni mode compared with the control was 0.9.Results: The estimated TP ratios and 95 % confidence intervals for total, major, and minor lesions were 0.87 (0.80 – 0.95), 0.93 (0.83 – 1.04), and 0.83 (0.74 – 0.94), respectively. Although non-inferiority was not demonstrated, the rate of detection of major lesions was not significantly different between the modalities. The reading time was significantly lower when using the Omni mode than when using the control.Conclusions: The Omni mode may be only appropriate for the assessment of major lesions.